An Investigation into the Use Level of Personal Information Management (PIM) by Faculty Members of Allied Medical Sciences Schools in Tehran, Shahid Beheshti and Iran Medical Sciences Universities in 2014 Year - Fereydoon Azadeh; Zahra Jadidi; Hamid Haghani (پیاورد سلامت, 2017)
Background and Aim: Creating personal information collections will bring the management needs. The purpose of this study was to determine the use level of personal information management and each of its four activities by Faculty members of Allied Medical Sciences Schools in Tehran, Shahid Beheshti and Iran Medical Sciences Universities in 2014 year. Materials and Method: This applied study was an analytical survey. The participants of the study were Faculty members of Allied Medical Sciences Schools in Tehran, Shahid Beheshti and Iran Medical Sciences Universities. All participants (120) were studied. PIM was surveyed by using a questionnaire. Descriptive statistics were used for data analysis. In order to determine the significant differences, analytical statistics were applied. The validity was confirmed by the number of professors feedback and reliability calculated by the Cronbachchr('39')s alpha 0.91. Results: Storage with average of 73.59% and organization with average of 62.11% were at "good" level. Maintenance with an average of 54.4% and refind with an average of 59.93% were at "medial" level. "Personal information management" with an average of 62.51% was at "good" level. According to the research hypotheses test, the use of personal information management and each of its elements by members of the community in terms of university, academic rank and gender were not statistically significant. Conclusion: Usage level of personal information management by faculty members is far from ideal situation. The main reasons can be included not having enough time, working pressure and lack of sufficient acquaintance with the activities required to personal information management.